PHARMACEUTICAL PRODUCT DEVELOPMENT : INSIGHTS INTO PHARMACEUTICAL PROCESSES, MANAGEMENT & REGULATORY AFFAIRS - DISOWZA, PATRAVALE V., RUSTOMJEE (NEW YORK CRC PRESS)
HB
TEXT BOOK
PH
Keywords: PHARMACEUTICS